2021
DOI: 10.1016/j.csbj.2021.01.023
|View full text |Cite
|
Sign up to set email alerts
|

The impact of episporic modification of Lichtheimia corymbifera on virulence and interaction with phagocytes

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…albicans have developed different strategies to evade immune detection either via modification in their cell-wall constituents or secretion of inhibitory fungal molecules ( 28 , 40 , 55 59 ). In contrast to the previous pathogenic fungi, the most virulent strain of L. corymbifera (FSU: 009682) did not exhibit avoidance of immune detection by monocytes and neutrophils since its sporangiospores were rapidly and efficiently phagocytized by both cell types ( Figure 1A ), which suggests the presence of highly immunogenic molecules in its cell wall, such as β-1,3-glucans, as shown in L. corymbifera germlings ( Figure S5 ), or unmasked chitosan after removal of glucans ( 60 ). However, recognition of an attenuated strain of L. corymbifera (FSU:10164) was reduced approximately by half when compared to the virulent strain ( Figure S1B ), indicating possible differences in the cell wall composition of each strain, which could influence on their virulence.…”
Section: Discussionmentioning
confidence: 99%
“…albicans have developed different strategies to evade immune detection either via modification in their cell-wall constituents or secretion of inhibitory fungal molecules ( 28 , 40 , 55 59 ). In contrast to the previous pathogenic fungi, the most virulent strain of L. corymbifera (FSU: 009682) did not exhibit avoidance of immune detection by monocytes and neutrophils since its sporangiospores were rapidly and efficiently phagocytized by both cell types ( Figure 1A ), which suggests the presence of highly immunogenic molecules in its cell wall, such as β-1,3-glucans, as shown in L. corymbifera germlings ( Figure S5 ), or unmasked chitosan after removal of glucans ( 60 ). However, recognition of an attenuated strain of L. corymbifera (FSU:10164) was reduced approximately by half when compared to the virulent strain ( Figure S1B ), indicating possible differences in the cell wall composition of each strain, which could influence on their virulence.…”
Section: Discussionmentioning
confidence: 99%
“…For this extended intracellular concealment, it applies several strategies, including melanization and metabolic adaptation, and inhibits the host cell apoptosis of polymorphonuclear cells by inducing autocrine IL‐8 production (Acorci et al, 2009). Furthermore, it has been shown that the resting conidia of A. fumigatus and Mucorales species can inhibit apoptosis of macrophages as well (Andrianaki et al, 2018; Hassan et al, 2021; Volling et al, 2011), securing their extended intracellular phase.…”
Section: Persistencementioning
confidence: 99%
“…In addition, both genera induce phagosome maturation arrest mediated by cell wall melanin and the calcineurin signal pathway in Rhizopus ( Andrianaki et al., 2018 ) and Mucor species ( Lee et al., 2015 ; Vellanki et al., 2020 ), respectively. Resting spores of Lichtheimia corymbifera also inhibits the intracellular acidification of macrophages in vitro , independently from melanin ( Hassan et al., 2021 ).…”
Section: Understanding the Fungal Response To The Macrophage Attackmentioning
confidence: 99%